Mutual Impact of Personal Income Tax and Macroeconomic Indicators - Ćurčić, Mihailo; Milojević, Irena; Krunić, Nikola (Industrija, 2020)
From mid-2006 to the end of 2008, a series of decisions were adopted in the public finances of the Republic of Serbia, which resulted in a permanent reduction in tax revenues and an increase in public expenditures. This creates a systemic imbalance between government revenue and expenditure, that is, the fiscal deficit. The emergence of the fiscal deficit is the main motive of the conducted research, where using a simple regression analysis of the time series of macroeconomic data, we linked the indicators of economic growth and personal income tax. The results of the research speak of the importance of the influence of personal income tax on the creation of a favorable macroeconomic environment, where the regulation and reform of the existing tax system are imposed as imperatives.